2011
DOI: 10.1192/bjp.bp.110.086827
|View full text |Cite
|
Sign up to set email alerts
|

Pressures to adhere to treatment (‘leverage’) in English mental healthcare

Abstract: BackgroundCoercion has usually been equated with legal detention. Non-statutory pressures to adhere to treatment, ‘leverage’, have been identified as widespread in US public mental healthcare. It is not clear if this is so outside the USA.AimsTo measure rates of different non-statutory pressures in distinct clinical populations in England, to test their associations with patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 17 publications
2
33
0
Order By: Relevance
“…Legal detention plays a large part in the experience of coercion but is not the only important factor. Country of study was also a significant variable, with coercion less common in the USA, even after controlling for the relative distribution of legal detention, when 40 with increased pressure ('leverage') applied in a US setting. This highlights the importance of clearly defining the construct examined, in this case coercion as opposed to leverage, and how these are defined.…”
Section: Discussionmentioning
confidence: 99%
“…Legal detention plays a large part in the experience of coercion but is not the only important factor. Country of study was also a significant variable, with coercion less common in the USA, even after controlling for the relative distribution of legal detention, when 40 with increased pressure ('leverage') applied in a US setting. This highlights the importance of clearly defining the construct examined, in this case coercion as opposed to leverage, and how these are defined.…”
Section: Discussionmentioning
confidence: 99%
“…Patients meet non-statutory pressure and coercion, although they are in voluntary in-or out-patient care. Burns et al (2011) studied social pressure and leverage in USA and UK and found that some measures of social pressure vary by country. Using non-statutory pressure is associated with the severity of mental illness and substance use (Burns et al 2011).…”
Section: Coerced Patients' Perceptions Of Their Overall Treatmentmentioning
confidence: 99%
“…Indeed, since it is already known (Burns et al 2011) that 'leverage' amongst mental health populations exists, how much more likely is it to occur in an imprisoned population? We do not know the answer.…”
Section: (Iii) Coercionmentioning
confidence: 99%